Double Rectangle Fascia Lata Frontalis Sling: A Rationale Approach for Ptosis - Pawan Agarwal; Dhananjaya Sharma; Vikesh Agrawal; Swati Tiwari; Rajeev Kukrele (Indian Journal of Plastic Surgery)
Background The purpose of this study was to evaluate the functional outcomes of a modified technique of double rectangle pattern for correction of severe ptosis. Methods This is a retrospective study over a period of 8 years including patients who underwent correction of ptosis by double rectangle using autologous fascia lata sling. Surgical outcomes were assessed postoperatively by distance from the corneal light reflex to the upper eyelid margin (MRD1) and levator function. Results Twenty-six eyelids were operated in 20 patients. There were 9 males and 11 females, with age ranging from 4 to 35 years. Preoperatively, all patients had poor MRD1 and poor levator function. Postoperative MRD1 was good in 13 patients (17 eyelids), fair in 5 (7eyelids), and poor in 2 patients (2 eyelids). Postoperative levator function was excellent in 12 patients (15 eyelids), good in 6 (9 eyelids), and fair in 2 patients (2 eyelids). At a mean follow-up of 12 months, adequate correction was achieved in 24 eyelids, and 2 eyelids had undercorrection. Conclusion Frontalis sling with a double rectangle is simple and more efficient, as it provides a straight line of pull to the eyelid for correction of severe ptosis.